2017
DOI: 10.1186/s12864-016-3415-6
|View full text |Cite
|
Sign up to set email alerts
|

Spread of avian pathogenic Escherichia coli ST117 O78:H4 in Nordic broiler production

Abstract: Background Escherichia coli infections known as colibacillosis constitute a considerable challenge to poultry farmers worldwide, in terms of decreased animal welfare and production economy. Colibacillosis is caused by avian pathogenic E. coli (APEC). APEC strains are extraintestinal pathogenic E. coli and have in general been characterized as being a genetically diverse population. In the Nordic countries, poultry farmers depend on import of Swedish broiler breeders which are part of a breeding pyramid. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 34 publications
3
60
1
1
Order By: Relevance
“…In general, phylogroup G strains are uncommon. However, STc117 is the most prevalent phylogroup G lineage and is commonly isolated from poultry and poultry meat products in Northern Europe (Ronco et al, 2017) and Canada (Bergeron et al, 2012). Recently, it has been shown in the East of England that ST117 represents 8% and 20% of livestock (poultry and pigs) and poultry meat E. coli isolates respectively (Ludden et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In general, phylogroup G strains are uncommon. However, STc117 is the most prevalent phylogroup G lineage and is commonly isolated from poultry and poultry meat products in Northern Europe (Ronco et al, 2017) and Canada (Bergeron et al, 2012). Recently, it has been shown in the East of England that ST117 represents 8% and 20% of livestock (poultry and pigs) and poultry meat E. coli isolates respectively (Ludden et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the results of our study are similar to those obtained in Denmark, where the parent flocks which did not receive ceftiofur but for which the grandparent flocks received cephalosporins (19), demonstrated a 93% prevalence of cephalosporin resistant E. coli (most of the samples being positive for bla CMY-2 ). Vertical transmission of APEC from breeders to their progeny is well known (2) and has been demonstrated recently in the Nordic countries where APEC ST117 O78:H4 was transmitted from grand-parent flocks to their broilers in different countries (31). In addition, Nilsson et al demonstrated the vertical transmission of E. coli carrying bla CMY-2 from grand-parent flocks which had been exposed to ceftiofur to parent and broiler flocks which had never received ceftiofur (29).…”
Section: Discussionmentioning
confidence: 99%
“…Two isolates were assigned to ST117 (phylogenetic group F). Recent studies indicate that this sequence type comprises important APEC lineages that are repeatedly reported from colibacillosis outbreaks in different countries (25,37,(40)(41)(42), but are also highlighted as potential zoonotic pathogens for containing ExPEC-related virulence genes and being isolated from both retail poultry meat and human clinical urinary tract infections (43). The remaining phylogroup F isolate was ST354, another potentially zoonotic ST, reported particularly from human and animal healthcare facilities and characterized by common resistance to antimicrobials including uoroquinolones (44,45).…”
Section: Discussionmentioning
confidence: 99%